A compact von Hámos spectrometer for parallel X‐ray Raman scattering and X‐ray emission spectroscopy at ID20 of the European Synchrotron Radiation Facility. (2nd December 2022) - Sahle, Ch. J.; Gerbon, F.; Henriquet, C.; Verbeni, R.; Detlefs, B.; Longo, A.; Mirone, A.; Lagier, M.-C.; Otte, F.; Spiekermann, G.; Petitgirard, S.
Abstract : A new X‐ray spectrometer in von Hamos geometry for parallel X‐ray Raman scattering and X‐ray emission spectroscopy is available at the inelastic X‐ray scattering beamline ID20 of the ESRF. Abstract : A compact spectrometer for medium‐resolution resonant and non‐resonant X‐ray emission spectroscopy in von Hámos geometry is described. The main motivation for the design and construction of the spectrometer is to allow for acquisition of non‐resonant X‐ray emission spectra while measuring non‐resonant X‐ray Raman scattering spectra at beamline ID20 of the European Synchrotron Radiation Facility. Technical details are provided and the performance and possible use of the spectrometer are demonstrated by presenting results of several X‐ray spectroscopic methods on various compounds.